MEMBERI SERASA MENERIMA: Dinamika Pondok Pabelan dan K.H. Hamam Dja’far 1938-1993 - Husein Haikal (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
This article tries to present the perception of Islam among the ‘rural’ inhabitants. Some consider it as a traditionalist perception. However, the differ-ences between traditionalist and reformist or modernist wings in Indonesian Islamic history are still questionable. This Islamic perception especially deals with its education, not only in the matter of ta’lim, or tarbiyah, but also deals with ta’dib. Since it is limited by available space, this article only focuses on the dinamic aspects of the Islamic attitude and practices of Kiai Haji Hamam Dja’far in reviving of Pondok Pesantren Pabelan. His success makes him known not only in the national but also in the international level, as shown in 1980 when Mr. Hamam got The Aga Khan Award for Architecture. Besides receiving this distinghuish award, Pondok Pabelan also got the fund amount of US 10.000., this fund was considered as an additional fund to develop the Pondok Pabelan.